Merdeka Curriculum Management Based on Character Education in The Millennial Generation - Ismy Wulansari; Murni Yanto (Institut Agama Islam Negeri Sorong, 2022)
In this modern era n educational institutions, have demands to develop IPTEK demi the creation of quality outputs, so that students can develop creatively and can keep up with the times of the global era. And the morality of the lives of children (students) is now encountered many problems directly and on social media. from these problems, this study aims to analyze and describe how independent curriculum management is based on character education in the millennial generation. This research method uses a descriptive qualitative methodology based on books, journals and articles. This technique focuses on how to manage an independent character-based curriculum and efforts to form a millennial generation with character.